Defect formation and strain relaxation in graded GaPAs/GaAs, GaNAs/GaAs and GaInNAs/Ge buffer systems for high-efficiency solar cells - Schoene, J.; Spiecker, E.; Dimroth, F.; Bett, A. W.; Jaeger, W. (Journal of Physics: Conference Series, 2013)
Transmission electron microscopy of cross-section specimens and high-resolution X-ray diffraction analyses have been applied to investigate the formation of defects and the relaxation of layer strain in step-graded GaP xAs1-x and GaNyAs1-y buffer layer systems grown by metal-organic vapour phase epitaxy on GaAs (001) substrates with 6° miscut towards (111)A. The investigations have been complemented by characterization of the layer surfaces employing optical microscopy. The comparison of the different buffer concepts reveals characteristic differences in the formation of defects and in the relaxation of tensile layer strain. For GaPAs layers dislocations and microtwins form, releasing the major part of the tensile misfit strain. In contrast, for GaNAs dislocations and microtwins are largely absent, at least in the upper part of the buffer structure, and microcracks are generated. Consequently, during subsequent growth of layers with tensile strain, strain relaxation and defect formation can be effectively hindered by introducing intermediate GaNyAs1-y layers with concentrations y > 2 % into a GaAs1-xPx buffer structure [1]. A similar concept can be used for layer systems with compressive strain, however, modified by using layers of differing alloy composition. The use of dilute nitride layers appears to offer a new concept for engineering defect distributions and layer strain in lattice-mismatched compound semiconductor layer structures. Such concepts are of particular interest not only but especially also for applications in high-efficiency III-V solar cells.
CRIS-Team Scopus Importer:2023-03-17